Frozen Mother’s Own Milk Can Be Used Effectively to Personalize Donor Human Milk - Torrez Lamberti, Monica F.; Harrison, Natalie A.; Bendixen, Marion M.; DeBose-Scarlett, Evon M.; Thompson, Sharon C.; Neu, Josef; Parker, Leslie Ann; Lorca, Graciela L. (Frontiers in Microbiology, 2021)
Feeding preterm infants mother’s own milk (MOM) lowers rates of sepsis, decreases necrotizing enterocolitis, and shortens hospital stay. In absence of freshly expressed MOM, frozen MOM is provided (FMOM). When MOM is unavailable, preterm infants are often fed pasteurized donor human milk (DHM), rendering it devoid of beneficial bacteria. We have previously reported when MOM is inoculated into DHM to restore the live microbiota (RM), a similar microbial diversity to MOM can be achieved. Yet, it is unknown if a similar diversity to MOM can be obtained when FMOM is inoculated into DHM. The goal of this study was to determine whether a similar microbial composition to MOM could be obtained when FMOM is used to personalize DHM. To this end, a fresh sample of MOM was obtained that was divided into fresh and frozen fractions. MOM and FMOM were inoculated into DHM at different dilutions: MOM/FMOM 10% (RM/FRM10) and MOM/FMOM 30% (RM/FRM30) and incubated at 37°C. At different timepoints, culture dependent and culture independent techniques were performed. Similar microbiota expansion and alpha diversity was observed in MOM, RM10 and RM30 whether fresh or frozen milk was used as the inoculum. To evaluate if microbial expansion would result in an abnormal activation on the innate immune system, Caco-2 epithelial cells were exposed to RM/FRM to compare IL-8 levels with Caco-2 cells exposed to MOM or DHM. It was found that RM samples did not elicit a significant increase in IL-8 levels when compared to MOM or FMOM. These results suggest that frozen MOM can be used to inoculate DHM if fresh MOM is unavailable or limited in supply, allowing both fresh and frozen MOM to be viable options in a microbial restoration strategy.